A live fuel moisture climatology in California - Drucker, Jack R.; Farguell, Angel; Clements, Craig B.; Kochanski, Adam K. (Frontiers in Forests and Global Change, 2023)
In this study, the live fuel moisture content (LFMC) for predominantly sampled live fuels in eight distinct regions of California were examined from 2000 to 2021. To gather the necessary data, an open-access database called the Fuel Moisture Repository (FMR), was developed. By harnessing the extensive data aggregation and query capabilities of the FMR, which draws upon the National Fuel Moisture Database, valuable insights into the live fuel moisture seasonality were obtained. Specifically, our analysis revealed a distinct downtrend in LFMC across all regions, with the exception of the two Northernmost regions. The uptrends of LFMC seen in those regions are insignificant to the general downtrend seen across all of the regions. Although the regions do not share the same trends over the temporal span of the study, from 2017-2021, all the regions experienced a downtrend two times more severe than the general 22-year downtrend. Further analysis of the fuel types in each of the eight regions, revealed significant variability in LFMC across different fuel types and regions. To understand potential drivers of this variability the relationship between LFMC and drought conditions were investigated. This analysis found that LFMC fluctuations were closely linked to water deficits. However, the drought conditions varied across the examined regions, contributing to extreme LFMC variability. Notably, during prolonged drought periods of two or more years, fuels adapted to their environment by stabilizing or even increasing their maximum and minimum moisture values, contrary to the expected continual decrease. These LFMC trends have been found to correlate to wildfire activity and the specific LFMC threshold of 79% has been proposed as trigger of an increased likelihood of large fires. By analyzing the LFMC and fire activity data in each region we found that more optimal local thresholds can be defined, highlighting the spatial variability of the fire response to the LFMC. This work builds upon previous literature about correlations between drought and LFMC as well as between fire activity and LFMC. This study provides a 22-year dataset of LFMC across the entirety of California and analyzes the LFMC trends in California that haven’t been rigorously studied before.